Peningkatan Pengetahuan Rambu Lalu Lintas melalui Penyuluhan kepada Ibu-Ibu PKK di Desa Cimanggis, Kabupaten Bogor - Eko Primadi Hendri; Aan Sunandar; Torang Hutabarat; Tatang Adhiatna; Sulistyo Sutanto; Sarah Fadhlia (Indo Publishing, 2026)
Limited public understanding of the functions and meanings of traffic signs may affect traffic discipline and increase the risk of traffic violations and accidents. Women members of the Family Welfare Empowerment (PKK) organization play a strategic role as educators within their families; therefore, improving their knowledge of traffic signs is expected to have a broader impact on community traffic safety awareness. This community service program aimed to improve the participants’ knowledge of traffic sign classifications, functions, and meanings through lectures, interactive discussions, and demonstrations. The activity was conducted in RT 001/RW 001, Cimanggis Village, Bojonggede District, Bogor Regency, involving 17 PKK members. The effectiveness of the program was evaluated using a one-group pretest–posttest design. Data were analyzed using descriptive statistics, followed by the Shapiro–Wilk normality test and a paired-samples t-test. The results showed that the mean score increased from 4.65 in the pretest to 7.53 in the posttest, representing an improvement of 2.88 points. The Shapiro–Wilk test indicated that the data were normally distributed (p = 0.207), while the paired-samples t-test revealed a statistically significant improvement in participants’ knowledge after the educational intervention (t = −6.255, p < 0.001). Furthermore, 76.47% of the participants achieved a posttest score of at least seven, meeting the predetermined success indicator. These findings demonstrate that lecture-based education combined with discussion, demonstration, and visual learning media is effective in improving community knowledge of traffic signs and supporting the development of a traffic safety culture within families and the wider community.